Reeds Western Mediterranean almanac 2008. (Adlard Coles Nautical, 2007)
A navigation guide to the Western Mediterranean containing detailed chartlets and easy to access navigation and harbour information in both English and French. It covers the areas of South and East Spain, the French Mediterranean coast, Northern Italy, the Western Mediterranean and the islands of Balearics, Corsica, Sardinia, Sicily, and Malta.